PRX1 knockdown potentiates vitamin K3 toxicity in cancer cells: a potential new therapeutic perspective for an old drug. Issue 1 (December 2015) - He, Tiantian; Hatem, Elie; Vernis, Laurence; Lei, Ming; Huang, Meng-Er
Abstract Background Many promising anticancer molecules are abandoned during the course from bench to bedside due to lack of clear-cut efficiency and/or severe side effects. Vitamin K3 (vitK3) is a synthetic naphthoquinone exhibiting significant in vitro and in vivo anticancer activity against multiple human cancers, and has therapeutic potential when combined with other anticancer molecules. The major mechanism for the anticancer activity of vitK3 is the generation of cytotoxic reactive oxygen species (ROS). We thus reasoned that a rational redox modulation of cancer cells could enhance vitK3 anticancer efficiency. Methods Cancer cell lines with peroxiredoxin 1 (PRX1) gene transiently or stably knocked-down and corresponding controls were exposed to vitK3 as well as a set of anticancer molecules, including vinblastine, taxol, doxorubicin, daunorubicin, actinomycin D and 5-fluorouracil. Cytotoxic effects and cell death events were evaluated by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT)-based assay, cell clonogenic assay, measurement of mitochondrial membrane potential and annexin V/propidium iodide double staining. Global ROS accumulation and compartment-specific H2 O2 generation were determined respectively by a redox-sensitive chemical probe and H2 O2 -sensitive sensor HyPer. Oxidation of endogenous antioxidant proteins including TRX1, TRX2 and PRX3 was monitored by redox western blot. Results We observed that the PRX1 knockdown in HeLa and A549 cells conferred enhanced sensitivity to vitK3, reducing substantially the necessary doses to kill cancer cells. The same conditions (combination of vitK3 and PRX1 knockdown) caused little cytotoxicity in non-cancerous cells, suggesting a cancer-cell-selective property. Increased ROS accumulation had a crucial role in vitK3-induced cell death in PRX1 knockdown cells. The use of H2 O2 -specific sensors HyPer revealed that vitK3 lead to immediate accumulation of H2 O2 in the cytosol, nucleus, and mitochondrial matrix. PRX1 silencing significantly up-regulated mRNA and protein levels of NRH:quinone oxidoreductase 2, which was partially responsible for vitK3-induced ROS accumulation and consequent cell death. Conclusion Our data suggest that PRX1 inactivation could represent an interesting strategy to enhance cancer cell sensitivity to vitK3, providing a potential new therapeutic perspective for this old molecule. Conceptually, a combination of drugs that modulate intracellular redox states and drugs that operate through the generation of ROS could be a new therapeutic strategy for cancer treatment.